2005
DOI: 10.1016/j.ijgo.2005.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum extraction and herpes simplex virus infection

Abstract: Herpes simplex virus isolated from the scalps of newborns may often result from colonization rather than infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The age at diagnosis of the vesicular eruption of VAD ranged from 0.9 to 41.7 hours . In a follow‐up study at the same institution, the authors postulated that HSV might be colonizing the lesions rather than a pathologic process . In both studies, no patients demonstrated a positive colony‐stimulating factor PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age at diagnosis of the vesicular eruption of VAD ranged from 0.9 to 41.7 hours . In a follow‐up study at the same institution, the authors postulated that HSV might be colonizing the lesions rather than a pathologic process . In both studies, no patients demonstrated a positive colony‐stimulating factor PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Complications include chignon (artificial caput succedaneum), retinal hemorrhage, neonatal jaundice, cephalohematoma, subgaleal hemorrhage, abrasions, and lacerations . Vesiculation has been reported secondary to VAD with a higher risk of herpes simplex virus (HSV) .…”
mentioning
confidence: 99%